Design of a Containerized Greenhouse Module for Deployment to the Neumayer III Antarctic Station - Bamsey, Matthew; Zabel, Paul; Zeidler, Conrad; Poulet, Lucie; Schubert, Daniel; Kohlberg, Eberhard; Graham, Thomas (2014)
Designs for an Antarctic plant production system to be deployed at Germany’s Neumayer Station III are presented. Characterization and testing of several key controlled environment agriculture technologies are ongoing at the German Aerospace Center’s Institute of Space Systems. Subsystems under development at the Evolution and Design of Environmentally-Closed Nutrition-Sources (EDEN) laboratory include, tuned LED lighting, aeroponic nutrient delivery, ion-selective sensors and modular growth pallets. The Antarctic greenhouse module baseline form factor is a standard sea shipping container, which allows for use of nominal Antarctic logistics networks. The facility will be fixed onto a specially constructed platform and co-located near the Alfred Wegner Institute’s Neumayer Station III. The plant production facility will be operated year-round with maximum production per unit volume achieved through the deployment of modular grow units in a stackable rack architecture. In such a configuration the greenhouse module system can provide several kilograms of fresh edible biomass per day. Forty foot and 20 ft container configurations are described as well as the general design requirements, including specifics relevant to operations at Neumayer III. Successful deployment of such a facility will further the technology readiness and operational experience of space-based bioregenerative life support systems. Finally, the general design is presented in the context of an historical review of past Antarctic plant production facilities. This first known inventory of documented Antarctic plant production facilities, organizes the facilities with respect to Antarctic station, dates of operation, internal/external configuration and estimated production area.